Educar para a cidadania por meio da programação da tevê pública: a experiência da TVE de Porto Alegre/RS - Pereira, Fabiana da Costa (2018)
This research has as its theme the citizenship education in public TVs, delimited in subjects related to educational TV, looking specifically to the programs of the local TVE of Porto Alegre, RS. The central issue proposed to problematize the theme is defined in the question: how can public TV trigger citizenship education strategies from its own programming? The justification for its execution is the urgent need for changes in the conformation of the Brazilian communication system that is configured with the commercial channels in the open system and most of the public communication channels in the paid system. This proposal for change will only take place with pressure from the population at the National Congress to review the public concessions of the Brazilian broadcasting sector. In this sense, we understand that it is the role of public communication itself to educate the population in the pursuit of citizenship, including in this perspective the right to communication, considering the right to receive, produce and disseminate information. Actions that will lead to the democratization of the communication in the country and the real purpose of public communication, which should complement the private and public system. The general objective of this study is to analyze the citizenship education strategies triggered by the broadcast of the local TVE of Porto Alegre. The specific objectives seek to problematize the understanding of citizenship education in the context of a public TV; to investigate the local broadcast by TVE of Porto Alegre and to identify the citizenship education strategies of the local TV. The methodology is qualitative in nature, carried through a case study. The method of analysis is based on the textual analysis of audiovisual material, from Casetti and Chio (1999). In the final considerations, we identified some steps already taken by TVE towards a citizenship education throughout strategies that are present in the programming, like the presence of different groups, the perception of various perspectives, space for local events that depart from the reality of the communities, detail information, between others. However, at the same time, there is a maintenance of the journalistic practices of commercial vehicles, especially regarding the format of the programs and forms of participation that are still very linked to interviews. In this sense, it is urgent to think about the “how to” of journalism and the protagonist role of the population in a perspective where citizenship education becomes effective.